The Impact of an App on Students’ Anxiety, Well-Being, and Resilience: A Pilot Efficacy Study - Nicolaidou, Iolie (My University, 2023)
Post the COVID-19 pandemic, students need help to cope with elevated levels of anxiety and to be resilient. The Student Stress Resilience (SSResilience) app was designed to support undergraduates’ resilience through scaffolding goal setting of healthy activities (studying, social interaction, and physical exercise). Students’ goals are tracked using phone sensors (Internet of Things) and self-reports. The app was demonstrated to a sample of 24 students, 11 of whom used it after class for two weeks (experimental group), while 13 constituted the control group. All students were pre-tested and post-tested with respect to their anxiety, well-being, and resilience. Preliminary descriptive statistics for the experimental group showed a decrease in anxiety from Mpre = 7.30 (SD = 6.57) to Mpost = 5.20 (SD = 4.78) (percentage change = −30%), an increase of well-being from Mpre = 64/100 (SD = 30.98) to Mpost = 73.6/100 (SD = 20.84) and an increase of resilience from Mpre = 66.5 (SD = 19.8) to Mpost = 74.75 (SD = 14.02) (percentage change = 22%) after using the app. On the contrary, control group students’ measurements remained unchanged with respect to anxiety, had a very slight increase in well-being and a slight decrease in resilience. Preliminary findings indicate a potential value of the SSResilience app for increasing students’ resilience and well-being and reducing anxiety.
Keywords: Higher Education; Internet of Things (IoT); Mental Health App; Resilience